PUPULAN TEKS CERPEN ALIKAN GUMI KARYA I NYOMAN MANDA: ANALISIS SOSIOLOGI SASTRA - Ida Ayu, Widyastari (Humanis, 2015)
This study discuss about collection of short story of Alikan Gumi with structure analysis and literature sociology. This analysis have purpose to reveal narrative structure and social aspect written in collection of short story of Alikan Gumi. There were six short story, and data source in this study was Undangan, Bui Liang, SesambangGalang Ring Villa SangginganUbud, NgremengMaklieng, Malukat ka Selukat and Alikan Gumi. This study was applied structural theory and literature sociology. Structural theory by applied combination from some opinion from expert of literature as follows: Ratna and Teeuw and literature sociology theory by applied opinion from Damono, Wallek and Warren. Method and technique in this study consist of three steps that are (1) data providing step was applied reading method and interview with recording technique, translation and recording (2) data analysis steps was applied analitic descriptive qualitative method (3) data analysis result presentation steps was applied informal method helped with deductive-inductive technique. The result obtained in this study that are revealed the narrative structure consist of incidence, path, actor and characterization, background, theme and commendation. This study also to analyze social aspect that found in six short story in collection of Alikan Gumi that covering: religion aspect consist of philosophy aspect (tattwa), ethic aspect (susila), and ritual aspect (upakara), then love aspect, education aspect, art aspect, profesion aspect, and social aspect.
Keywords: short story, structure, social aspect.